2016
DOI: 10.1111/gtc.12384
|View full text |Cite
|
Sign up to set email alerts
|

Proplatelet formation in megakaryocytes is associated with endoplasmic reticulum stress

Abstract: Although previous studies suggest that proplatelet formation in megakaryocytes involves caspase-3, the mechanism underlying the activation of caspase-3 is unknown. Here, we analyzed caspase activation in a human megakaryoblastic cell line, MEG-01, which forms proplatelets spontaneously. Specific activation of caspase-3 and caspase-4 was found in proplatelets. Consistent with previous observations of caspase-4 autoactivation in response to endoplasmic reticulum (ER) stress, several ER stress marker proteins wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 44 publications
(52 reference statements)
1
20
0
Order By: Relevance
“…Houwerzijl et al (5) demonstrated increased vacuoles, plasma membrane thickening and chromatin condensation in the mitochondria and endoplasmic reticulum (ER) of ITP megakaryocytes. This may result in endoplasmic reticulum stress, leading to autophagy (6,7). Autophagy is a biological process, where cytoplasmic macromolecules self-degrade through the lysosomal pathway (8).…”
Section: Introductionmentioning
confidence: 99%
“…Houwerzijl et al (5) demonstrated increased vacuoles, plasma membrane thickening and chromatin condensation in the mitochondria and endoplasmic reticulum (ER) of ITP megakaryocytes. This may result in endoplasmic reticulum stress, leading to autophagy (6,7). Autophagy is a biological process, where cytoplasmic macromolecules self-degrade through the lysosomal pathway (8).…”
Section: Introductionmentioning
confidence: 99%
“…A recent report suggested that endoplasmic reticulum stress could be responsible for their activation. 66 Identification of caspase targets that are cleaved in mature MK would be a convincing evidence to support the hypothesis that caspase activation is required for platelet shedding and provide insights on how the localized activation of caspases contributes to platelet formation. One of these targets could be the antiapoptotic protein livin that belongs to the inhibitor of apoptosis proteins (IAP) family.…”
Section: Caspases In Proplatelet Formation and Platelet Releasementioning
confidence: 93%
“…The formation of platelets is mediated by ER stress. Using ER stressor, caspase-4 was inhibited in the megakaryocytes, which enhanced platelets production (91). However, the detailed mechanism is still not clear.…”
Section: Other Immune Cellsmentioning
confidence: 99%